Ajaran tentang Bakti Istri kepada Suami dalam Serat Wulang Reh Putri - Mirya Anggraeni; Suyanto Suyanto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Educating literature is a literary genre that contains teachings, whether about behavior in society or teachings on how to reach perfection of life according to Javanese tradition. One of the literary texts of educating (piwulang) is Serat Wulang Reh Putri (SWRP) by Paku Buwana IX from Surakarta. The work contains educational values for women, especially for wifes. This teaching was imparted to women since childhood. The teachings in the text emphasize the importance of women to obey husbands. A wife according to SWRP must obey the command and prohibition of husband, respect and devoted to the husband also and must know the character of her husband. Therefore, married to a woman does not rely on physical beauty but kindness.